THE EFFECTS OF THE IMPLEMENTATION OF 2013 CURRICULUM TO STUDENTS’ ENGLISH LEARNING ACHIEVEMENT AT SMAN 1 ALLA’ ENREKANG - Nur Humairatul Ulya (Universitas Islam Negeri Alauddin Makassar, 2015)
The objective of this research was to find out whether or not the implementation of 2013 curriculum give effects to the development of students’ English achievement at the second grade of SMAN 1 Alla’ Enrekang. This research was a descriptive design using observation, questionnaires, and documentation conducted at the second year of SMAN 1 Alla’ Enrekang class MIA 1 and IIS 2 in academic year of 2014/2015. The total sample of this research consisted of 61 students. The data were collected through observation in the class when the learning process conducted to know how the implementation of the 2013 curriculum and questionnaire as supporting data from observation while documentation to know the students’ learning achievement that was analyzed by descriptive and statistic. The data analysis and interpretation indicated (1) The implementation of the 2013 curriculum in SMAN 1 Alla’ Enrekang was good. (2) Learning achievement using the 2013 curriculum and KTSP was good. (3) There is no difference between students’ English learning achievement using different curriculum. It could be concluded that the learning achievement was not only influenced by the curriculum, but also many other factors for example the teachers or the facilities. In other words, the 2013 curriculum did not give effect to students’ English learning achievement